«Quotation and Literary Echo as Structural Principles in Gabriele Wohmann's Frühherbst in Badenweiler.» - Walter H. Sokel (Studies in 20th & 21st Century Literature, 1980)
In her novel of 1978, Wohmann uses the montage technique—quotations, literary echoes, erudite allusions—of the «classics of modernism» to put the contemporary West German phenomenon of «New Inwardness» in an ironic light. Her protagonist, the composer Hubert Frey, retreats from the stresses of contemporary life to the Black Forest spa of Badenweiler. New Inwardness in him appears allied to New Conservatism which, in reaction to the New Left of the sixties, revives the old German ideal of the «A-Political Man.» Echoing a work of restaurative mentality, Stifter's Nachsommer, Frey's Frühherbst looks back nostalgically on Goethe's classicist phase. As Goethe put his Storm and Stress behind him, Frey analogously repudiates the turbulent youth of the sixties. He sums up his ethos of withdrawal by quoting a passage from one of Goethe's letters. He quotes inaccurately and his self-identification with Goethe rests on shaky foundations. By revealing her protagonist's erudition as faulty and confused, Wohmann unmasks his whole stance as—literally—false. Another of Frey's models, Conrad Aiken, a writer of inwardness and subjectivity, turns out to have been the wrong author for Frey's choice of Badenweiler. The American writer who had actually sojourned there turns out to have been the realist Stephen Crane. Inwardness thus proves literally incorrect and inappropriate to the protagonist's needs. The displacement of the symbolist Aiken by the realist Crane points ahead to the conclusion of the novel. Whereas a World War had been needed to dislodge Thomas Mann's Hans Castorp from his retreat, a mere mouse, invading Frey's hotel room, serves the analogous function in Wohmann's novel. Literary echo, a structural device, functions thematically as both the symptom and the cure of her protagonist's passing relapse into German inwardness.
Keywords: Wohmann; montage technique; quotations; literary echoes; erudite allusions; classics of modernism; West German; New Inwardness; New Conservatism; A-Political Man; German; Stifter; Nachsommer; Frey; Frühherbst; Badenweiler; Thomas Mann; Hans Castorp